Modernidade e colonialismo: o conceito de vida nua com e para além de Giorgio Agamben - Batista, Tarciano Silva (2024)
This work aims to problematize the concept of bare life as lives that can be killed with impunity by sovereign decision, as initially formulated by the Italian philosopher Giorgio Agamben. To this end, we define as the object of analysis the texts from the Homo Sacer project, with emphasis on the first volume: Sovereign Power and Bare Life (1995). The thesis to be defended investigates the relationship between life and politics when, divided and articulated through the power of the sovereign, life (human, citizen, conscious, and free) becomes a qualified form, while giving rise to another formless (identity-less) and impunely disposable life: bare life. In this context, politics becomes a bio-necropolitics, that is, a calculated organization and management of individuals' lives and deaths, justified as a politics of exception. Thus, we perceive that, in Agamben, bare life materializes in the space known as the "camp," which becomes the main Western political paradigm. Following this perspective, our hypothesis is that the concept of bare life has its paradigmatic roots in the figure of Homo Sacer in antiquity. However, during modernity, it manifests in the life of the enslaved during colonialism and extends to the contemporary era, exemplified by figures like the Musselman in Auschwitz. This triad — colonialism, Nazism, and fascism — exemplifies how different regimes of power, using control technologies and policies of exception, shaped and justified bio-necropolitics. Thus, we engage in discussions of Political Philosophy, seeking to contribute to the undeniable fact that all existing forms of the camp constitute crimes against humanity and constant factories of lives that can be killed with impunity.